Ensuring HIV care to undocumented migrants in Israel: a public-private partnership case study - Daniel Chemtob; Rivka Rich; Neta Harel; Nechama Averick; Eyal Schwartzberg; Israel Yust; Shlomo Maayan; Itamar Grotto; Ronni Gamzu (BMC, 2019)
Abstract Background Undocumented migrants in Israel, mostly originating from HIV endemic countries, are not covered by Israel's universal healthcare coverage. We initiated a Public-Private Partnership (PPP) to handle this public health and humanitarian challenge. The PPP venture included the Ministry of Health (MoH), pharmaceutical companies, pharmacies, and specialized HIV clinics, the Israeli HIV Medical Society (from the Israel Medical Association), and non-governmental organizations. This study describes the national policy process in conceptualizing and implementing access to HIV services for undocumented migrants through a PPP, and analyzes the preliminary results. Methods This case study describes the process of creating a temporary Public-Private Partnership to provide HIV care for undocumented migrants based on institutional records of the Department of Tuberculosis and AIDS (DTA) and memories and reflections from partners. This case was analyzed according to the OECD-DAC criteria for development assistance (relevance, effectiveness, efficiency, sustainability and impact). Demographic and serological data of patients referred between 2014 to 2018 were collected to monitor progress. and analyze preliminary medical and biological outcomes. Ethical approval was obtained from the Ministry of Health. Results Creating a policy to extend HIV care to undocumented migrants was a 15 year process that confronted several challenges within Israeli and international discourse, particularly concerning governmental response to the migration crisis. The use of a PPP model involving numerous stakeholders provided a solid, local feasibility demonstration that extending HIV care as a matter of policy would have positive implications for public health in Israel. During the first 2 years of the program (2014-2015), the MoH funded medical follow-up and the pharmaceutical companies provided antiretroviral treatment (ART) free of charge for only 100 patients at any given time, in addition to ART provided by the MoH for pregnant women. Since 2016, the MoH has fully covered this service and integrated it within the Israeli health system; this constitutes the major success of the PPP program. As of December 2018, the national program has monitored 350 patients and treated 316 (90.3%). The most prevalent disease present upon referral was Tuberculosis. Conclusions To our knowledge, this study documents the first example of a successful PPP with government partnership in a high-income country to address undocumented migrants' lack of access to health services in general and HIV care in particular. In light of the intensification of North-South migration, this Israeli case study could be useful for other countries facing similar challenges. It also has lessons within Israel, as the country grapples with other health problems among uninsured communities.